The Oxford handbook of higher education systems and university management - Redding, S. G.; Drew, Antony; Crump, Stephen (Oxford : Oxford University Press, 2019)
Examines the main challenges facing higher education systems in an increasingly turbulent and interconnected world, exploring how higher education institutions are managed in changing conditions, and the societal implications of different approaches to change.
The Description and Comparison of Societal Systems of Higher Education and University Management / Gordon Redding, Antony Drew, Stephen Crump -- Critical Factors and Forces Influencing Higher Education in the 21st Century / Antony Drew, Gordon Redding, Trevor Harley -- A New World of Communications in Higher Education and Its Implications / Liam Phelan, Antony Drew, Andrew Yardy -- Leading in Higher Education / Maurits van Rooijen -- Policy and Practice in University-Business Relations / Ewart Keep -- Implications of changing influences for equality, social and gender justice in HE / Miriam E. David, Penny Jane Burke, Marie-Pierre Moreau -- Macro Changes and the Implications for Higher Education Research / Tracy Robinson, Kylie Twyford, Helena Teede, Stephen Crump -- Canada in a Global System of Higher Education: The Role of Community Engagement / Brent Epperson, Britta Baron, Carl G. Amrhein -- Developing and Maintaining Transnational Research Collaborations: A Case Study of Australian Universities / Fazal Rizvi, Ranjit Gajendra Nadarajah -- Scholarship in the University: An Ecological Perspective / Ronald Barnett -- Criticality, Academic Autonomy, and Societal Progress / Gordon Redding -- Higher Education Finance: Global Realities, Policy Options, and Common Misunderstandings / D. Bruce Johnstone -- Educating for the Cooperative Society: The Role of Government in Building Human and Social Capital / Ken Mayhew -- Educating for the Cooperative Society: The Role Of Industry in Building Human And Social Capital / Suzanna Tomassi -- Educating for the Cooperative Society: The Role Of Universities, Research, and the Academic Professions in Fostering Good Citizenship / Mehmet Murat Erguvan, Nikoloz Parjanadze, Kevin Hirschi -- Governments Need To, and Do, Trust Universities / Mike B. Calford -- Education and Technological Unemployment in the Fourth Industrial Revolution / Michael A. Peters, Petar Jandrić -- Education for the Innovative Society: The Role of Indian Institutes of Technology in India / Venni V. Krishna, Nimesh Chandra -- Policy Implications for Equity, Gender, and Widening Participation in Higher Education / Penny Jane Burke, Miriam E. David, Marie-Pierre Moreau -- Socializing Human Capital for 21st Century Educational Goals: Suggestive Empirical Findings from Multi-National Research / Michael H. Bond, Yiming Jing -- Maintaining the Contribution of Higher Education to Societal Progress / Gordon Redding, Stephen Crump, Antony Drew -- Reactions, Reflections, and Renewal: The Significance of Higher Education for Intellectual, Social, and Personal Advancement / Stephen Crump -- Changing the Nature and Role of Universities: The Effects of Funding and Governance Reforms on Universities as Accountable Actors / Richard Whitley -- Recent Trends in East and West University Governance: Two Kinds of Hollowness / Gabriel Donleavy, Kuan-Cheng Chen -- Cycles of Evolution of Ideal Types of Universities: Causes and Consequences for the University Mission - The Case of Poland / Svetlana Gudkova, Anna Pikos, Valentyna Guminska -- The Implications of a Diversifying Workforce for Institutional Governance and Management in Higher Education / Celia Whitchurch -- The Collegial Tradition in English Higher Education: What Is It, What Sustains It, and How Viable Is Its Future? / David Palfreyman, Ted Tapper -- Managing a University in Turbulent Times / Gordon Redding, Antony Drew, Trevor Harley.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 24, 2019).
Keywords: Education, Higher; Universities and colleges -- Administration; Education, Higher -- Social aspects; Education; Education